Komunikasi Pada Pelatihan Adaptasi Perubahan Iklim (Program Pelatihan CDCCAA Di Kecamatan Panguragan Kabupaten Cirebon) - Afnida Shoffati Noorfajria; Djuara P Lubis; Resfa Fitri (Institut Pertanian Bogor, 2015)
Farmers have local wisdom passed down from generation to generation as a guide in farming activities. However, the existence of climate change makes them must be able to adapt to new agricultural patterns. They are required to know in advance the appropriate planting season in order to avoid crop failure later. Nonetheless, the farmers who are figure most susceptible to this problem are precisely not to have such knowledge. For these reasons the Ministry of Agriculture in collaboration with JICA (Japan International Cooperation Agency) create a training program that is devoted to improving the adaptability of farmers in the face of climate change named CDCCAA (Capacity Development for Climate Change Adaptation in Agriculture and Other Relevant Sectors). The present study was aimed to evaluate the factors that influence of the communications programs that are indicated by the farmers' knowledge about climate change, the attitude of farmers facing climate change and the farmers tendency to act after the training. Based on the survey of 50 trainees in the Panguragan Subdistrict Cirebon Regency, and SEM analysis it is known that the individual characteristics significantly influence the communication process CDCCAA training program, and cosmopolity factors have also significant influence on the behavior of farmers against the risk of climate change. In addition, the communication process not significantly influence with attitudes to climate change risk, and assessment of training rogram not significantly influence with communication process also.Keywords: climate change, process of communication , adaptation